2021
DOI: 10.1080/22797254.2021.1918582
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Landsat-8 OLI and Sentinel-2 MSI images for estimating the ecological quality of port waters

Abstract: Recent research has demonstrated that the TRophic IndeX (TRIX) is informative on the ecological quality of Mediterranean port waters and can be estimated by the processing of multispectral observations collected in situ. The current study investigates the alternative use of multispectral data acquired by medium-high spatial resolution optical satellite sensors, i.e. the Landsat-8 (L8) Operational Land Imager (OLI) and the Sentinel-2 (S2) MultiSpectral Instrument (MSI). The study analyzes the impact of the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The exploration of this possibility is based on the pioneering work of Massi et al (2019) [27], which showed how hyperspectral observations taken in situ are informative on the TRIX levels of port waters. Pieri et al (2021) [28] confirmed this possibility using high spatial resolution multispectral imagery taken from satellite platforms. A further study [29] extended the analysis to the use of multispectral observations taken by the Sentinel 3 mission through the Ocean and Land Color Instrument (OLCI) sensor, which is particularly suitable for monitoring medium-scale seawater phenomena.…”
Section: Related Work and Research Objectivesmentioning
confidence: 76%
“…The exploration of this possibility is based on the pioneering work of Massi et al (2019) [27], which showed how hyperspectral observations taken in situ are informative on the TRIX levels of port waters. Pieri et al (2021) [28] confirmed this possibility using high spatial resolution multispectral imagery taken from satellite platforms. A further study [29] extended the analysis to the use of multispectral observations taken by the Sentinel 3 mission through the Ocean and Land Color Instrument (OLCI) sensor, which is particularly suitable for monitoring medium-scale seawater phenomena.…”
Section: Related Work and Research Objectivesmentioning
confidence: 76%